Effect of drying techniques on quality and sensory properties of tropical fruits. (8th September 2022) - Petikirige, Jasmine; Karim, Azharul; Millar, Graeme
Summary: Drying is a popular food preservation technology that reduces food waste and promotes food preservation and food security. Though drying reduces microbial growth and increases shelf life of fruits, it alters sensory properties both favourably and unfavourably depending on the nature of the drying process applied and significantly influences the final product quality. However, there is currently no review article on the impact of the drying process on the sensorial quality attributes of tropical fruits. This review attempts to describe the relative merits and challenges of some widely used advanced drying techniques with a particular focus on intermittent microwave convective drying (IMCD) techniques which offer high sensory properties with excellent drying efficiency. The paper aims to provide an insight into the effect of these drying techniques on the sensory qualities of tropical fruits to identify the best drying method for future food applications. Abstract : Fruits and vegetables, particularly the tropical fruits are very rich in nutrition. Due to high moisture content and seasonality, tropical fruits are highly perishable. Drying is widely used to reduce the food waste and increase the self life. However, properties of fruits are significantly changed during drying depending on the drying process applied. Currently, there is no review article on the impact of the drying process on the sensorial quality attributes of tropical fruits. This review article addresses this research gap and investigates the impact of some widely used advanced drying on the sensory qualities of tropical fruits.